If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 103 + -3x = 15x + 23 Reorder the terms: 103 + -3x = 23 + 15x Solving 103 + -3x = 23 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 103 + -3x + -15x = 23 + 15x + -15x Combine like terms: -3x + -15x = -18x 103 + -18x = 23 + 15x + -15x Combine like terms: 15x + -15x = 0 103 + -18x = 23 + 0 103 + -18x = 23 Add '-103' to each side of the equation. 103 + -103 + -18x = 23 + -103 Combine like terms: 103 + -103 = 0 0 + -18x = 23 + -103 -18x = 23 + -103 Combine like terms: 23 + -103 = -80 -18x = -80 Divide each side by '-18'. x = 4.444444444 Simplifying x = 4.444444444
| .44y^2+1=0 | | 3(y+2)-2=2(4-y) | | 3(y+2)-2=2(41y) | | 5s-19s=28 | | 4t+3=t-18 | | 8+2x*3=x*4+12 | | a^2x+3x=2a^2 | | x^2-5.75+7.75=6 | | x^2-5.75+7.75=1 | | x^2-5.75+7.75=4 | | x^2-5.75+7.75=2 | | 2x^2-4x+8.8=2 | | 2x^2-4x+18.2=2 | | 5a^2-6a=1 | | (10b-6)-3(3b+2)=-3 | | x^2-8x+15.75=0 | | y=0(0)-7 | | (4y+9)(4y+9)=64y^3+432y^2+972y+729 | | 5c+6=2-y | | 5x+6x+3+8=3x+5+7x | | 16+-8-9= | | z^2-8z-20= | | 3(Q-6)=2(2Q+7)+10 | | 25+-15-12= | | 15x^2+5x-20= | | y=18(0)+0 | | 9y^2+21y+6= | | 2x+3x=30-z | | y=-7(0)+4 | | 3x^2-4y=20 | | 3x^2-4y=20 | | 5(t-3)+7t=4(3t+3)-10 |